2007
DOI: 10.1128/mcb.00355-07
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic AMP-Stimulated Interaction between Steroidogenic Factor 1 and Diacylglycerol Kinase θ Facilitates Induction of CYP17

Abstract: In the human adrenal cortex, adrenocorticotropin (ACTH) activates CYP17 transcription by promoting the binding of the nuclear receptor steroidogenic factor 1 (SF1) (Ad4BP, NR5A1) to the promoter. We recently found that sphingosine is an antagonist for SF1 and inhibits cyclic AMP (cAMP)-dependent CYP17 gene transcription. The aim of the current study was to identify phospholipids that bind to SF1 and to characterize the mechanism by which ACTH/cAMP regulates the biosynthesis of this molecule(s). Using tandem ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
79
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(86 citation statements)
references
References 123 publications
(160 reference statements)
7
79
0
Order By: Relevance
“…In contrast, inhibition of DGK activity attenuates the binding of SF1-dependent gene expression, and silencing the expression of DGK expression inhibits cAMP-dependent CYP17A1 transcription. Finally, we have also shown that LXXLL motifs in DGK mediate a direct interaction of SF1 with the kinase and may facilitate ligand delivery ( 25 ). To date, studies have demonstrated that DGK is regulated by intracellular targeting ( 24 ), membrane lipids ( 12 ), protein-protein interactions ( 34 ), and intrinsic activity ( 12 ).…”
Section: Transient Transfection and Reporter Gene Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…In contrast, inhibition of DGK activity attenuates the binding of SF1-dependent gene expression, and silencing the expression of DGK expression inhibits cAMP-dependent CYP17A1 transcription. Finally, we have also shown that LXXLL motifs in DGK mediate a direct interaction of SF1 with the kinase and may facilitate ligand delivery ( 25 ). To date, studies have demonstrated that DGK is regulated by intracellular targeting ( 24 ), membrane lipids ( 12 ), protein-protein interactions ( 34 ), and intrinsic activity ( 12 ).…”
Section: Transient Transfection and Reporter Gene Analysismentioning
confidence: 99%
“…We have previously shown that cAMP signaling increases the transcription of CYP17A1 by stimulating the binding of SF1 to the CYP17A1 promoter ( 32,33 ). We have also shown that DGK regulates the production of PA, a ligand for SF1 that is produced in response to cAMP signaling ( 25 ). DGK acts as a coregulatory protein by binding to SF1 when the receptor is bound to chromatin.…”
Section: Transient Transfection and Reporter Gene Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…This is a compelling approach to decipher endogenous ligand occupancy of orphan nuclear receptor in an in vivo setting. Sewer and colleagues were able to identify several phospholipids bound to another orphan nuclear receptor, steroidogenic factor 1 (SF-1) (Li et al 2007) with roles in the regulation of steroidogenic hormones expression. SF-1 was immunoprecipitated from adrenocortical cells which express the receptor endogenously and phospholipids were analysed by LC-MS. Phosphatidic acid was found to be a major lipid bound to SF-1 and to activate the transcriptional activity of the receptor.…”
Section: Targeted Identification Of Ligands For Nuclear Receptorsmentioning
confidence: 99%